2002
DOI: 10.2144/02331st03
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Binding Protein Assay for Widespread Use in Cell Signaling Studies

Abstract: cAMP plays a critical role in intracellular signaling pathways that regulate proliferation or differentiation. The cAMP binding protein assay, using a naturally derived cAMP binding protein, is one of the most widely used methods for cAMP determination. The major steps of this binding assay include purification of the binding protein, cAMP extraction from samples, and quantification of the cAMP Most purification methods of the cAMP binding protein were published before 1975, and many of the materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This analog binds to cell surface cAMP receptors and induces cAMP production and export, but it is not detected by the cAMP detection method we used (32, 33). We found that stimulation caused a twofold increase in the levels of extracellular cAMP in the wild type but no significant increase in the two abcB3 -RNAi cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analog binds to cell surface cAMP receptors and induces cAMP production and export, but it is not detected by the cAMP detection method we used (32, 33). We found that stimulation caused a twofold increase in the levels of extracellular cAMP in the wild type but no significant increase in the two abcB3 -RNAi cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, samples were neutralized using a 50% saturated solution of KHCO 3 , centrifuged, and the supernatant collected for the assay. 20 μL of tracer (0.4 μCi/mL of 3 H-cAMP), 20 μL of sample or standard, and 40μL of cAMP binding protein prepared from beef muscle (33) were combined and incubated on ice for 1.5 hours. Binding reactions were stopped by addition of 40μL activated charcoal.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on activation of both G s -and G i -coupled receptors are focus on cAMP [97]. The difference is that they lead adenylate cyclase activation (G s ) or inhibition (G i ), resulting in increased or decreased intracellular cAMP levels, respectively.…”
Section: G S and G I Pathwaysmentioning
confidence: 99%
“…The in vitro bioactivity of released PTH was determined by adenylate cyclase stimulation assay and cAMP binding protein assay as previously described [38,39]. Briefly, rat osteosarcoma cells (ROS 17/2.8) were treated with PTH (1-34) of known concentrations or with eluent from the PTH delivery device for designated times in calcium-and magnesium-free hanks' balanced salt solution (Invitrogen, Carlsbad, CA) containing 0.1% BSA and 1 mM isobutylmethylxanthine (IBMX).…”
Section: In Vitro Pth (1-34) Bioactivity Assaymentioning
confidence: 99%